Organizational performance and competitive advantage in SMEs: The role of green innovation and knowledge management - Fandi Achmad; Iwan Inrawan Wiratmadja (Journal of Open Innovation: Technology, Market and Complexity)
Small and Medium-sized Enterprises (SMEs) are vital to economic growth, job creation, and sustainable development. However, sustainability remains a challenge, especially for SMEs in developing countries facing resource limitations, market fluctuations, and technological constraints. Among them, Batik SMEs in Indonesia struggle with barriers to green innovation, such as limited knowledge, shifting market trends, rising production costs, and a lack of innovation, threatening long-term sustainability. This study examines the role of knowledge management (KM) in fostering green innovation (GI) and its impact on organizational performance (OP) and competitive advantage (CA) in Batik SMEs. A quantitative survey was conducted with 191 Batik SMEs in Rembang Regency and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The research model tests four hypotheses: The first hypothesis is that KM has a positive effect on GI; the second hypothesis is that GI improves OP; the third hypothesis is that OP strengthens CA, and the fourth hypothesis is that innovation capability moderates the relationship between KM and GI. The findings confirm that KM significantly enhances GI (β=0.401, p < 0.05), which positively influences OP (β=0.508, p < 0.05). Furthermore, OP strengthens CA. However, innovation capability does not significantly moderate the relationship between KM and GI (p > 0.05). These results highlight the crucial roles of knowledge management and green innovation in improving performance and competitiveness. SME owners and managers are encouraged to integrate green innovation into business strategies while strengthening internal capabilities to support sustainable practices. By doing so, Batik SMEs can enhance organizational performance, maintain market competitiveness, and achieve long-term sustainability.